Decomposition of the symptom observation matrix and grey forecasting in vibration condition monitoring of machines - Cempel, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
With the tools of modern metrology we can measure almost all variables in the phenomenon field of a working machine, and many of the measured quantities can be symptoms of machine conditions. On this basis, we can form a symptom observation matrix (SOM) intended for condition monitoring and wear trend (fault) identification. On the other hand, we know that contemporary complex machines may have many modes of failure, called faults.
Keywords: machine wear; multidimensional observation; vibrations; SVD decomposition; fault space; observation space; symptom limit value; forecasting; grey system theory